Developing Special Economic Zones (SEZs) In Malaysia: A Land Use Planning Legal Perspective - Najimudin, Muhammad Fadhlullah; Md Dahlan, Nuarrual Hilal; Md Nor, Mohd Zakhiri (Malaysia Institute of Planner (MIP), 2023)
Special Economic Zones (SEZs) are a known mechanism that policymakers commonly use to attract Foreign Direct Investment (FDI). However, there is a global mixed reaction towards its successful implementation with a few operational failures, especially from the legal framework perspective. Therefore, this paper aims to explore the land use planning legal issues encountered by the development of the Special Economic Zones in Malaysia. Two significant legal issues and problems focusing on the cases related to land use planning and land matters have been identified using qualitative textual analysis. Findings show that there are loopholes and weaknesses in the statutory plan and local authorities exercising their power on land use planning management-related matters. Thus, understanding the legal cases from these two issues is essential in formulating the next course of action on how the legal and regulatory framework should be embodied and embedded in the land use planning practice and policy in SEZs' development.